IMPLEMENTASI PERENCANAAN PENGELOLAAN DAN PEMANFAATAN HUTAN DESA DI KABUPATEN GUNUNGKIDUL - Suwarti Suwarti; M Saleh Soeaidy; Suryadi . (REFORMASI, 2015)
The absence of a management plan may hamper technical forestry activities. Another impact is the communication between peasants and forest officials obstructed, smallholder farmers lack the education or capacity building activities in forest areas are managed comprehensively. The method used is qualitative descriptive approach. Analysis of the data by using analysis Miles and Huberman. The implementation of planning seen through the four stages of the planning process is the stage of investigation, negotiation, implementation and evaluation. Factors supporting from social aspect that is government facilitating and readiness of management institutions. Ecological support of the AB land area availability. Economic support from timber prices increasing. While inhibiting factor derived from ecological aspects, namely natural barriers and geographical conditions. Social barriers from limited awareness and knowledge. Economic barriers due to lack of assistance and capital in forest management budget.